International nuclear diplomacy and India - Gupta, U. N. (New Delhi, 2007)
The present book is an in-depth systematized study of diversified efforts of States, statesmen and diplomats to prevent a nuclear war. It records the international concern for achievement of disarmament and prevention of proliferation of nuclear weapons as a common objective of all States. The cold-war rivalries, the collective security system of United Nations, the moves for disarmament of States involving nuclear weapons, the politics of maintaining the hegemony of five Superpowers, need for petrol leading to oil diplomacy of the West and several other factors associated with problems of new States have evolved into identifiable 'nuclear diplomacy' since 1960s. Keeping States away from nuclear weapons for achievement of national ambitions is seen as basic subject matter of nuclear diplomacy. The book examines the efforts of States to prevent proliferation of nuclear weapon technology in general and to such States in particular that might seek to use it for achieving national ambitions. Apart from the five Superpowers, Pakistan, North Korea, Iran, India, and Iraq have been under international scrutiny. In the book, case studies of these States have also been undertaken, since every State that seeks nuclear weapons has some enemies or evil designs. It has been felt necessary to adopt a sociological approach, that is, briefly going into the background histories of nuclear weapon sensitive States. The Superpower States are above the law of the UN Charter and have a combined rigid stance on the subject of transfer of nuclear technology. Other States seeking nuclear technology for energy production, for economic and civil purposes are left to original research or acquisition by clandestine methods. This aspect has also been examined in the book, keeping in view the interests of India. The book would be highly useful to a wide cross section of the reading public, including scholars and academics, government executives, international institutions and planners and policymakers.
Keywords: Nuclear diplomacy